The maternal viral threshold for antiviral prophylaxis of perinatal hepatitis B virus transmission in settings with limited resources: A large prospective cohort study in China. Issue 48 (4th December 2017) - Lu, Ying; Zhu, Feng-Cai; Liu, Jian-Xun; Zhai, Xiang-Jun; Chang, Zhan-Jun; Yan, Ling; Wei, Kai-Ping; Zhang, Xin; Zhuang, Hui; Li, Jie
Abstract: Background: Antiviral therapy has been documented to reduce perinatal transmission of hepatitis B virus (HBV) in highly viremic mothers. This large prospective cohort study conducted in China aims to delineate the maternal viral threshold for consideration of antiviral prophylaxis in settings with limited resources. Methods: A total of 1177 mother-infant pairs with positive maternal hepatitis B surface antigen (HBsAg) under current passive-active prophylaxis regimen were enrolled from community health centers in Jiangsu and Henan provinces, China. Maternal hepatitis B e antigen (HBeAg) status and viral load were tested at 36–40 weeks of gestation. Post-vaccination serologic testing was performed at 7 and 12 months of age. Results: HBeAg-positive mothers (419/1177; 35.6%) had significantly higher viral loads, compared with HBeAg-negative mothers (758/1177; 64.4%) (8.12 vs. 2.69 log IU/mL, p  < .0001). Twenty infants, born to HBeAg-positive mothers with high viral loads (median, 8.38; range: 7.82–9.22 log IU/mL), were infected at 7 months of age. In contrast, none of the HBeAg-negative mothers transmitted HBV to their offspring. After adjustment for the other risk factor, a higher maternal viral load was significantly associated with a higher risk of transmission (adjusted odds ratio, 3.78; 95% confidence interval: 1.46–9.81; p  = .006). The rates of passive-active immunoprophylaxis failure were 0.0% (0/789), 0.0% (0/27), 0.0% (0/32) and 6.1% (20/329) at maternal viral loads of <5, 5–6, 6–7 and ≥7 log IU/mL, respectively. The antibody to hepatitis B surface antigen (anti-HBs) response rate was 98.4% (1138/1157) at 7 months of age. Conclusions: Results from this study indicate that the maternal viral threshold associated with perinatal transmission of HBV is 7 log IU/mL, which may be appropriate for consideration of antiviral prophylaxis in settings with limited resources.